2019
DOI: 10.5964/jspp.v7i2.1127
|View full text |Cite
|
Sign up to set email alerts
|

Meaning-making and rumour-mongering in the shadow of terrorism: The case of the Charlie Hebdo attack in Paris

Abstract: The January 7, 2015 Charlie Hebdo terrorist attack in Paris shattered French civilians’ sense of security and also their sense of the surrounding world. This quasi-longitudinal study investigates the temporal dynamics of meaning-making and rumour-mongering processes of French civilians (N = 161) in a real-world, post-terrorist context. The present study was conducted via questionnaire at three points in time (i.e. one week, one month and two months) following the January 7, 2015 terrorist attack in Paris. In l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The level of terrorism shows that to finally decide to commit an act of terrorism (fifth floor) means to have passed the first floor and continue to the fourth to end on the fifth floor (Blackwood et al, 2016;Pelletier & Drozda-Senkowska, 2019;van Heelsum & Vermeulen, 2018). The pattern of levels of carried out by women in Indonesia, based on the results of research-onresearch subjects, it was found that the subjects were on two stairs, DYN, which had reached the fifth floor (fifth floor), and SN and NKD on the first floor.…”
Section: Women As Terrorists…mentioning
confidence: 99%
“…The level of terrorism shows that to finally decide to commit an act of terrorism (fifth floor) means to have passed the first floor and continue to the fourth to end on the fifth floor (Blackwood et al, 2016;Pelletier & Drozda-Senkowska, 2019;van Heelsum & Vermeulen, 2018). The pattern of levels of carried out by women in Indonesia, based on the results of research-onresearch subjects, it was found that the subjects were on two stairs, DYN, which had reached the fifth floor (fifth floor), and SN and NKD on the first floor.…”
Section: Women As Terrorists…mentioning
confidence: 99%
“…However, they also represent a complex psychosocial phenomenon that has been studied in a range of contexts. Rumours that have been investigated within real‐world settings have generally been collected, classified, and analysed by researchers in the context of unusual, dangerous or threatening real‐life situations, such as wars (e.g., Allport & Postman, 1947; Haque & Sabir, 1975; Knapp, 1944), riots (Bhavnani, Findley, & Kuklinski, 2009), terrorism (Pelletier & Drozda‐Senkowska, 2019), natural disasters, including earthquakes (Prasad, 1935), floods (Jacquart & Haas, 2006) and hurricanes (Thomas, 2007), organisational changes (Bordia, Jones, Gallois, Callan, & DiFonzo, 2006), financial speculations and crises (DiFonzo & Bordia, 1997; Kimmel, 2010; Roux‐Dufort & Pauchant, 1993), major health issues, such as cancer (DiFonzo, Robinson, Suls, & Rini, 2012) or the HIV and AIDS epidemics (Kimmel & Keefer, 1991; Smith, Lucas, & Latkin, 2010; Stadler, 2003), and in schools (Kieffer, Kiefer, 2013) and workplace bullying situations (Crothers et al, 2009).…”
Section: Empirical Investigation Of Rumour Transmissionmentioning
confidence: 99%